Synthesis of existing literature on the colorectal surgery patients’ challenges during hospital-to-home transitions: a scoping review protocol - Hardeep Singh; Karen Okrainec; Sami A Chadi; Ani Orchanian-Cheff; Auden Steane (BMJ Open)
Introduction Despite advances in innovation to improve patients’ transition experiences, it is unclear—in the context of colorectal surgery—what elements of patient education and care could provide the greatest benefit to patient experiences and clinical outcomes. Thus, this scoping review protocol aims to outline a plan to synthesise the existing literature from countries with publicly funded health systems (ie, Australia, Canada, France, Germany, the Netherlands, New Zealand, Sweden, the United Kingdom and the USA) on the challenges experienced by colorectal surgery patients’ when transitioning home from the hospital.Methods and analysis This is a protocol for a scoping review to identify literature relating to adult patient challenges experienced when transitioning from hospital to home following colorectal surgery. We will search the following databases for studies published between 2012 and present: Ovid MEDLINE; Ovid Embase; Cochrane Database of Systematic Reviews (Ovid) and Cochrane Central Register of Controlled Trials (Ovid). Title, abstract and full-text review will be conducted independently by at least two reviewers. Data will be extracted, collated, summarised and reported numerically (eg, frequency counts) and presented using descriptive summaries. In addition, data related to the challenges reported by colorectal surgery patients during their transition home from the hospital will be descriptively analysed using deductive content analysis. The extracted challenges will be categorised according to the International Classification of Functioning, Disability and Health and the surgical transition trajectory (eg, predischarge, during discharge and postdischarge) to identify when in the patient journey is the best point to implement improved practices and achieve patient-centred care.Ethics and dissemination This protocol does not require ethics approval as data have not been collected or analysed. The findings will highlight insights into patient care transitions following colorectal surgery, which will be disseminated via publications and presentations.